Pelatihan Pembuatan Media Pembelajaran Fisika Di SMA Negeri 2 Percut Sei Tuan Dengan Menggunakan Alat Praktikum 2025 /2026 - Pinondang Hutapea; Melda Panjaitan (JK2M : Jurnal Kemitraan Kepada Masyarakat, 2026)
Media can be defined in the context of educational activities as an entity that can convey information and understanding during conversations between students and teachers. When compared to other classical methods, the lecture method has many advantages, especially in terms of time efficiency. With the lecture method, teachers can control the speed of teaching because the duration of time is fully controlled by the teacher. This will better ensure that the target learning material will be achieved. In addition, the teacher's dominant position in the class will make it easier for teachers to control student learning behavior. Based on the analysis of the results of the activity, it can be concluded that after the training, students' awareness of the importance of knowing physics practicum tools and how to use them has increased. The students' motivation to develop an interest in learning physics has increased so that when new students are accepted, many are interested in the Academy of Radiodiagnostic and Radiotherapy Engineering.